Multicultural Education: Concept, Emergence and Dimensions - Tamang, Yam Bahadur (Innovative Research Journal, 2022)
Multicultural education is emerging perceptive in today’s education. Most of the educator and tutors need to aware how to treat the culture diversity of students in the teaching learning process. This cultural phenomenon basically influences on in building school structure and curricula implementation in school. This multicultural perspective emerged during the 1960s and more influential till now. It has cleared that this emerging concept needs to address for ensuring the equity in education of students. For this, Banks provided the five dimensions viz. content integration, knowledge construction process, prejudice reduction, equity pedagogy and an empowering school culture and social structure to address the cultural diversity of people in education.